Climate change drives a decline in global grazing systems - Chaohui Li; Maximilian Kotz; Prajal Pradhan; Xudong Wu; Yuanchao Hu; Zhi Li; Guoqian Chen (Proceedings of the National Academy of Sciences, 2026)
Grazing systems represent the most extensive production systems in the world and are highly sensitive to climate change. However, their global-scale sensitivity and vulnerability to climate impacts remain poorly understood. Here, we apply the safe climatic space framework to assess how changes in core climatic drivers of grazing suitability, including temperature, precipitation, humidity, and wind speed, will reshape global grassland-based grazing systems. Our analysis projects a net decline of 36 to 50% of areas in climate suitability for grazing by 2100, accompanied by inter- and intracontinental shift of grazing suitability. These changes are expected to negatively affect 110 to 140 million pastoralists and 1.4 to 1.6 billion livestock, with particularly severe impacts in Africa. We further show that 51 to 81% of these impacted populations reside in countries with low income, serious hunger, severe gender inequality, and high political fragility. Our study implies that future climate change will threaten grazing suitability across large portions of Earth, endangering the livelihoods of numerous communities and potentially triggering widespread socioeconomic consequences.